1988
DOI: 10.1111/j.1600-0447.1988.tb06416.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of chlorpromazine‐induced pigmentation with haloperidol substitution

Abstract: Four patients with chlorpromazine-induced pigmentation showed resolution of the condition on replacing chlorpromazine with haloperidol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Its limited reversibility led to attempts to treat the syndrome with depigmenting agents D-penicillamine and ascorbic acid, although the latter was not effective (Gibbard and Lehmann 1966). Alternatively, the pigmentary changes were dealt with by substituting different antipsychotic medications (Ewing and Einarson 1981; Thompson et al 1988; Lal et al 1993). Several pathophysiological mechanisms may be responsible for this condition: An inflammatory response to chlorpromazine might cause increased melanin deposition, potentially a direct cause of change in skin color.…”
Section: Nonneurological Side Effectsmentioning
confidence: 99%
“…Its limited reversibility led to attempts to treat the syndrome with depigmenting agents D-penicillamine and ascorbic acid, although the latter was not effective (Gibbard and Lehmann 1966). Alternatively, the pigmentary changes were dealt with by substituting different antipsychotic medications (Ewing and Einarson 1981; Thompson et al 1988; Lal et al 1993). Several pathophysiological mechanisms may be responsible for this condition: An inflammatory response to chlorpromazine might cause increased melanin deposition, potentially a direct cause of change in skin color.…”
Section: Nonneurological Side Effectsmentioning
confidence: 99%
“…Black galactorrhoea secondary to phenothiazines has also been reported 83 . In the case of chlorpromazine hyperpigmentation, it appears that the pigmentation generally reverses within months to years of discontinuing therapy, the use of other neuroleptics, including other phenothiazines, does not cause pigment disorders, and that lenticular changes persist, whereas corneal changes may slowly resolve 84–86 …”
Section: Other Adverse Cutaneous Reactionsmentioning
confidence: 99%
“…1,4 Rather, on the contrary, one study reported this drug to be a suitable alternative to chlorpromazine in patients with chlorpromazine-induced cutaneous pigmentation. 5 We can hypothesize that haloperidol-induced hyperpigmentation in our patients may be mediated by its effect on dopaminergic receptors. Even though the exact action of dopamine (DA) receptors is yet to be verified at the molecular and genetic level, ample literature remains supportive of the fact that D2 dopamine receptor (DRD2) activation inhibits melanogenesis, whereas DRD4 activation promotes it.…”
mentioning
confidence: 99%